2009
DOI: 10.1039/b914792f
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical evidence of charge transfer in weakly bound complexes of water

Abstract: We report the definitive assessment of a measurable (half a kJ/mol) charge-transfer (CT) component in the interaction of water with the noble gases. The CT is found to be strongly stereoselective and is mediated by a highly asymmetric, donor/acceptor concerted role of the two hydrogen atoms, which can in fact dictate the equilibrium geometry of the adducts. This finding may be of general relevance in explaining the known peculiar orientational features of water's interactions. By using an original method of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
108
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(120 citation statements)
references
References 22 publications
11
108
1
Order By: Relevance
“…High resolution molecular-beam scattering experiments, showing appreciable shifts in the position of quantum interference effects on the cross-section, 19 have, however, in some cases, suggested otherwise. Similar experimental findings, combined with very accurate ab initio calculations involving charge-displacement analysis, 20,21 have finally shown that even the waterÀnoble gas complexes cannot be classified as conventional noncovalent vdW systems: an appreciable (i.e., measurable) fraction of the interaction energy is due to CT. The latter was clearly demonstrated to be stereospecific, showing maximum strength for the noble gas (NG) approaching water on the hydrogen side.…”
Section: ' Introductionmentioning
confidence: 76%
“…High resolution molecular-beam scattering experiments, showing appreciable shifts in the position of quantum interference effects on the cross-section, 19 have, however, in some cases, suggested otherwise. Similar experimental findings, combined with very accurate ab initio calculations involving charge-displacement analysis, 20,21 have finally shown that even the waterÀnoble gas complexes cannot be classified as conventional noncovalent vdW systems: an appreciable (i.e., measurable) fraction of the interaction energy is due to CT. The latter was clearly demonstrated to be stereospecific, showing maximum strength for the noble gas (NG) approaching water on the hydrogen side.…”
Section: ' Introductionmentioning
confidence: 76%
“…The function Dq(z) was successfully introduced to study the chemical bond between gold and the noble gases [46] and also used to investigate charge transfer in weakly bound water adducts. [47,48] It defines, at each point z along a chosen axis, the amount of electron charge that, upon formation of the bond between the fragments, moves across a plane perpendicular to the axis through the point z. A positive (negative) value corresponds to electrons flowing in the direction of decreasing (increasing) z.…”
Section: Computational Details and Theoretical Aspectsmentioning
confidence: 99%
“…Kr-H2O was previously studied in the gas phase in the microwave (MW) range [5] and in matrix [6]. Gas-phase collision-type experiments supported by theoretical calculations were also published [7,8], as well as pure ab initio investigations [9][10][11][12][13][14]. According to the theoretical literature, the Kr atom is oriented quite on line with one of the water O-H bonds, thus in the water plane [8,11].…”
Section: Introductionmentioning
confidence: 99%